Impacto do padrão geométrico ventricular na remodelação cardíaca após o infarto do miocárdio - Farah, Elaine [UNESP]; Fusco, Daniéliso R. [UNESP]; Okumoto, Paulo R. R. [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Gaiolla, Paula Schmidt Azevedo [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Okoshi, Katashi [UNESP]; Zanati, Siméia G. [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP] (Sociedade Brasileira de Cardiologia (SBC), 2013)
BACKGROUND: The relevance of left ventricular (LV) geometric pattern after myocardial infarction is not known. OBJECTIVES: To analyze the presence of different LV geometric patterns and teir impact as a predictor of remodeling in patients with myocardial infarction. METHODS: Patients with anterior acute myocardial infarction (n = 80) were divided according to the geometric pattern: normal (normal left ventricular mass index [LVMI] and normal relative wall thickness [RWT]), concentric remodeling (normal LVMI and increased RWT), concentric hypertrophy (increased LVMI and RWT) and eccentric hypertrophy (increased LVMI and normal RWT). After six months, echocardiographic assessment was repeated. RESULTS: Four patients died. Of the survivors, 41 showed remodeling (R +), whereas 39 did not (R-). Considering the geometric pattern, the cases were distributed as follows: 24 patients with normal pattern, 13 with concentric remodeling, 29 with concentric hypertrophy and 14 with eccentric hypertrophy. Patients who showed remodeling had larger infarction sizes analyzed by peak CPK (R + = 4,610 (1,688-7,970), R- = 1,442 (775-4247), p <0.001) and CK-MB (R + = 441 (246 - 666), R- = 183 (101-465), p <0.001), trend towards higher prevalence of concentric remodeling (R+ = 10, R- = 3, p = 0.08) and lower prevalence of eccentric hypertrophy (R + = 2 R- = 12, p = 0.006). In the multivariate regression analysis, infarction size was a predictor (OR = 1.01, p = 0.020) and eccentric hypertrophy was a protective factor (OR = 0.189, p = 0.046) of ventricular remodeling after coronary occlusion. CONCLUSION: The LV geometric pattern of can have an impact on the remodeling process in patients with myocardial infarction.

FUNDAMENTO: A relevância do padrão de geometria após o infarto do miocárdio não é conhecida. OBJETIVOS: Analisar a presença de diferentes padrões de geometria ventricular esquerda (VE) e seu impacto como preditor de remodelação em pacientes com infarto do miocárdio. MÉTODOS: Pacientes com infarto agudo anterior (n = 80) foram divididos de acordo com o padrão de geometria: normal (índice de massa [IMVE] normal e espessura relativa da parede [ERP] normal), remodelação concêntrica (IMVE normal e ERP aumentada), hipertrofia concêntrica (IMVE e ERP aumentadas) e hipertrofia excêntrica (IMVE aumentado e ERP normal). Após seis meses, foi repetido o ecocardiograma. RESULTADOS: Quatro pacientes foram a óbito. Dos sobreviventes, 41 apresentaram remodelação (R+), enquanto 39 não remodelaram (R-). Considerando-se o padrão geométrico, houve a seguinte distribuição: 24 pacientes com padrão normal, 13 com remodelação concêntrica, 29 com hipertrofia concêntrica e 14 com hipertrofia excêntrica. Os pacientes que remodelaram apresentaram maiores tamanhos de infarto analisados pelo pico da CPK (R+ = 4.610 (1.688 - 7.970), R- = 1.442 (775 - 4.247), p < 0,001) e da CK-MB (R+ = 441 (246 - 666), R- = 183 (101 - 465), p < 0,001), tendência a maior prevalência de remodelação concêntrica (R+ = 10, R- = 3, p = 0,08) e menor prevalência de hipertrofia excêntrica (R+ = 2, R- = 12, p = 0,006). Na análise de regressão multivariada, o tamanho do infarto foi preditor (OR = 1,01; p = 0,020) e a hipertrofia excêntrica foi fator protetor (OR = 0,189; p = 0,046) de remodelação ventricular após a oclusão coronariana. CONCLUSÃO: O padrão de geometria ventricular pode ter impacto no processo de remodelação em pacientes com infarto do miocárdio.
Impact of ventricular geometric pattern on cardiac remodeling after myocardial infarction
Keywords: Remodelação Ventricular; Infarto do Miocárdio; Função Ventricular Esquerda; Hipertensão; Ventricular Remodeling; Myocardial Infarction; Ventricular Function; Left; Hypertension